The interstitial compartment as a therapeutic target in heart failure - Aronson, Doron (Frontiers in Cardiovascular Medicine, 2022)
Congestion is the single most important contributor to heart failure (HF) decompensation. Most of the excess volume in patients with HF resides in the interstitial compartment. Inadequate decongestion implies persistent interstitial congestion and is associated with worse outcomes. Therefore, effective interstitial decongestion represents an unmet need to improve quality of life and reduce clinical events. The key processes that underlie incomplete interstitial decongestion are often ignored. In this review, we provide a summary of the pathophysiology of the interstitial compartment in HF and the factors governing the movement of fluids between the interstitial and vascular compartments. Disruption of the extracellular matrix compaction occurs with edema, such that the interstitium becomes highly compliant, and large changes in volume marginally increase interstitial pressure and allow progressive capillary filtration into the interstitium. Augmentation of lymph flow is required to prevent interstitial edema, and the lymphatic system can increase fluid removal by at least 10-fold. In HF, lymphatic remodeling can become insufficient or maladaptive such that the capacity of the lymphatic system to remove fluid from the interstitium is exceeded. Increased central venous pressure at the site of the thoracic duct outlet also impairs lymphatic drainage. Owing to the kinetics of extracellular fluid, microvascular absorption tends to be transient (as determined by the revised Starling equation). Therefore, effective interstitial decongestion with adequate transcapillary plasma refill requires a substantial reduction in plasma volume and capillary pressure that are prolonged and sustained, which is not always achieved in clinical practice. The critical importance of the interstitium in the congestive state underscores the need to directly decongest the interstitial compartment without relying on the lowering of intracapillary pressure with diuretics. This unmet need may be addressed by novel device therapies in the near future.